Konut Mutfaklarının Analizi Ve Minimum Mutfak Tasarımı - Pak, Zeynep (Fen Bilimleri Enstitüsü, 1993)
Mutfak, bir konutta yer alan mekanların en önemlisidir. Bir ev kadını çalıştığı zamanın çoğunu mutfakta geçirmektedir. Tez konusu olarak "Minimum Mutfak Ünitesi" tasarımı seçilmiştir. Minimum mutfak, mutfakta gerçekleştirilen eylemlerin ve ekipmanların birbiriyle mümkün olduğu kadar birleştirildiği kompakt bir ünitenin minimum alan ve hacim kaplayacak şekilde tasarlanması ile oluşmaktadır. Bu ünitenin gerçekleştirilebilmesi için mutfak konusu bütün yönleri ile ele alınmıştır. 1. Bölüm'de çalışmanın amaçlan ve konunun seçilme nedenleri anlatılmış ve izlenen çalışma metodu belirtilmiştir. 2. Bölüm'de Türklerde mutfak ve yöresel özellikler üzerinde durulmuş ve Türk yemeğinin tarihçesi, yemek yeme alışkanlığını etkileyen etkenler ve Türk mutfağında değişmenin nedenleri anlatılmıştır. 3. Bölüm'de konut mutfaklarının analizi yapılmıştır. Mutfakta yapılan günlük eylemler ve rasyonel çalışma sırası belirlenmiştir. Kullanıcıların antropometrik ölçülerine göre, çeşitli ülkelerde ve ülkemizde kabul edilen boyut ve yükseklikler tablolarla gösterilmiştir. Daha sonra mutfak tipleri incelenmiş ve I, L, H. U, G tipi mutfakların özellikleri anlatılmıştır. 4. Bölüm'de hazır mutfak piyasasında bugünkü durum incelenmiş ve piyasadaki hazır mutfak tipleri (ithal mutfaklar, yerli - yabancı işbirliği mutfaklar ve yerli mutfaklar) anlatılarak, mutfak üreten ve satan firmaların çalışma sistemleri ve kullandıkları malzemeler anlatılmıştır. 5. Bölüm'de minimum mutfağın ortaya çıkma nedenleri üzerinde durulmuştur. Minimum mutfağın kullanıcıları belirlenmiş ve kullanıldığı mekanlar anlatılmıştır. Literatür araştırması yapılarak, minimum mutfağa örnek teşkil edebilecek tasarımlar çizimlerle gösterilmiştir. 6. Bölüm'de ise, minimum mutfak I tipi mutfaklardan oluştuğu içni, I tipi mutfaklarda ekipmanların yan yana gelişlerine göre oluşabilecek mutfak kombinasyonları gösterilmiştir. I tipi mutfaklarda yer alabilecek ekipmanlara karar verilmiş ve belirlenen kabullere göre gerçekleştirilen "MİNİMUT'un fonksiyonları anlatılmış, Minimut'u oluşturan modüller çizimlerle gösterilmiştir. Sonuçlarda ise böyle bir üniteye neden gerek duyulduğu ve gerçekleştirilmesi halinde sağlayacağı faydalar üzerinde durulmuştur.

Kitchen, is one of the most important elements in a house. Majority of poeple, especially house women spend most of their time in kitchens. Turkish life style has been dramatically changing and a prominant development and modernization phase have been seen. This dramatic change in the life style, has also influenced our houses, therefore, it has been passed from the old Turkish house to the modern house and also global residences made by using new technologies and materials. Admittedly, the prominant change in the life style, has an impact on eating habits. Since, the eating habits changed, kitchens have been reformed. The close relations between Turkish and western kitchens, getting the working life of Turkish women, rising of cultural level of Turkish poeple have reformed the traditional ordinary life style into modern life style, and so Turkish kitchen. The aim of this study, is to make a minimum kitchen design which can be taken part in small residences, touristical establishments, offices and department stores. The equipments and the realized functions depend on the size, physical conditions of kitchens and the life style and the habits of people. A minimum kitchen is occured by designing a compact unit in which the actions such as cooking, washing, serving and equipments such as fridge, hob, oven are come together as much as possible so as to cover a minimum area and volume. That kind of a unit, if it's technical base and electrical connections are convenient, can provide all the needed functions of a kitchen. Minimum kitchen unit is needed in a lot of places. A pprominant increase in building of studio styled residences and user demands have been seen in the last years. This kind of residences are usually preferred by young and new married people. This residences usually include a unique room, bathroom, sitting place and open kitchen units. The minimum kitchen units in this kind of houses have completely been able to accomplish all the functions of an open kitchen. It also provides realization of some actions like cooking, heating, and preparing etc., as a secondary kitchen, without going to the main kitchen in the big houses. The tourism potential of our country has an extraordinary development phase in the last years and therefore a dramatic increase in the number of hotels, holiday villages and small pensions and hostiles. Especially in the holiday resorts, people who want to convert their residences into small hotel and pensions, provide the poepli who stay there, to cook and prepare theirown meals just by bringing the needed water and electrical connections. vi Meanwhile,same investers who have apart hotels consturcted and exploited, have been able to meet kitchen requirements of users just by bringing and connecting a minimum kitchen unit. Another area in which the minimum kitchen unit is used, are offices and shops. It is possible to obtain a useful kitchen place with a minimum allocation by establishing this unit in offices and shops. The main target of using that kind of a minimum kitchen unit is to meet the user needs in the places, stated before. It is aimed that it will create a convenient market as a result of its usefulnes and low cost. Then daily actions made inthe kitchen are determined and working places of these actions and also equipments taking part in this places are explained. By classifying the main actions realized in kitchens, the relations between these actions and antropometric measurements of users have discussed. All dimensions in equipments have determined by the data indicating the antropometric measurements of users both in our country and in different foreign countries so as to obtain maximum productivity from the action made in this unit. These dimensions have been used in determining the dimensions of minimum kitchen unit in the subsepuant parts of this study. After all of these informations and explanations, kitchenes have been classified according to the forms of worktops in the plans and then all the specifications of each type kitchen have been explained. All of these explanations have been supported by the kitchen technical drawingns. In the subsequent parts of the study, firms that sells ready kitchens, their production type and methods have been scrutinized and also, by some face toface interviews with especially owners of firms, their working, operation and production systems and using materials have been analysed. Same breakdowns of firms, explaining their adresses, operating systems and their material alternatives have been give however, a table has been created by scrutinizgn dimensions and heights that these firms use for their kitchen boardks. After scrutinizing the ready kitchen market in Turkey, the real reason that why it is need a minimum kitchen unit, is discussed. Then the user groups and their main requirements for a nümmum kitchen unit have been analysed and by the help of a small study of literature, some minimum kitchen examples have been explained and these explanations have been supported by drawing and photos. vu In part one, before designing the minimum kitchen unit, the aim of this study and the methods that have been followed are explained. In part two placement, position and specifications of kitchen in the traditional Turkish house have been scrutinized by giving some examples from different regions of Turkey, on the other hand, characteristic specifications of the traditional Turkish meals, main factors influencing the eating habits and global reasons of changing in the Turkish kitchen are explained, then, the real impacts of changing life style and habits to kitchen design are discussed. In the third part of the study, the critic typological analys of an average residence witchen has been made and therefore daily actions and the order of rational operations have been determined. The preminant forms of dimensions and other measurements as hegihts of modular units, having both an international and local acceptances have been indicated by soma detailed matrixes and tables according to their on thropometric size and measures. After that, several kitchen types like I, L H, U, G and their specifications have been extensively explained with respect to the forms that they are constitude in the specific plans. In part four, the ruling conditions and current market perspective in the ready to use kitchen sector have been drawn comprehensively. The operational systems and mainly utilized materials that the companies which produce and sell phose ready to use, modular kitchen systems, have been explained and then marketable or the best selling performanig kitchen types (e.g. imported kitchen moduls, goint renture produced kitchens) have been discussed with their ruling market track records. In the fifth part, the main reasons of occuring of said minimum kitchen in the market are discussed. Some explanatory examples with regards to also those minimum kitchens effectively designed before, taken also part in this section. The endusers of "minimum kitchens" and the arrent market, picture have been annlysed and then the possible reasons for using thiskind of a modular kitchen system in residences, touristic buildings, offices and several kinds of stores have been discussed. As a result of all analysis, a new product: "MINIMUT" has been developed in the last part of the study. All the needed moduls that cnostitudes the "MINIMUT" have been defined by combining determined dimension and mesurements. After a deep analys of usable materials, some comments and technical results have been examined.
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 1993
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 1993
Keywords: Konut mimarisi; Mutfak tasarımı; Housing architecture ;Kitchen design